PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN KESATUAN BANGSA DAN POLITIK KOTA MAKASSAR - Risman, Risman; Pratiwi, Yayu Chandra (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
The Influence of Work Environment and Work Discipline on Employee Performance at the Makassar City National Unity and Politics Agency. This study aims to determine the influence of the Work Environment and Work Discipline on Employee Performance at the Makassar City National Unity and Politics Agency. The population in this study was 44 employees at the Makassar City National Unity and Politics Agency. A sample of 44 respondents was taken. The data collection method used primary data obtained from distributing questionnaires. The analysis technique used in this study was multiple regression analysis. Based on the results of the study, it is known that the environment has a significant effect on employee performance, while work discipline has a significant effect on employee performance at the Makassar City National Unity and Politics Agency.